Does Fiscal Decentralization Affect Poverty? An Empirical Study - Ariyani Widyastuti; Agung Nusantara (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
The Poverty percentage in Central Java ranked two throughout Java Island after DI Yogyakarta Province. It surely causes gaps and inequality between regions in Central Java Province. This study attempted to analyze the effects of fiscal decentralization, fiscal balance fund, and economic growth on the poverty in 35 regencies/ cities in Central Java Province within 2016-2020. By using a quantitative approach, this study used a panel analysis with a Fixed Effect Model (FEM) method. Based on the results of panel data regression analysis results, fiscal decentralization and fiscal balance fund had no relationship with the poverty in Central Java. On the other hand, economic growth had positive and significant effects. High economic growth will reduce poverty rate when the economic activities carried out are padat karya which aims at absorbing workforce. High workforce absorption will reduce the poverty rate.